“Acompañamiento para el examen de habilitación para el ejercicio profesional de la carrera de Enfermería” - Llivi Ruilova, Danny Vicente (2024)
In the auditorium of the Faculty of Health and Human Sciences of the UEB, the “Support for the qualification exam for the professional practice of the Nursing career” was carried out, which had as facilitators, to Dr. Silvana López Paredes, dean; Mgtr. María Olalla, career coordinator and Dr. Felipe Rivera, teacher; with the participation of 115 students, who this weekend will take their exam in different places in the country.